C1. Maternal hemodynamic profile in hypertensive disorders of pregnancy (HDP) and intrauterine growth restriction. (12th August 2016) - Di Martino, D.; Zullino, S.; Casati, D.; Grimaldi, A. S.; Mastroianni, C.; Principato, G.; Rosti, E.; Garbin, M.; Ferrazzi, E.
Abstract: Aims : To investigate maternal hemodynamic status in pregnancies complicated by HDP and/or IUGR and by severe IUGR without HDP. Methods : In this prospective study we enrolled pregnant women between 24 and 38 weeks divided in: HDP with appropriate for gestational age fetuses (HDP-AGA), HDP associated with IUGR (HDPIUGR), severe IUGR and a group of controls matched for gestational age. Severe IUGR was defined as abdominal circumference <5th centile and a Doppler velocimetry in umbilical artery42SD. Diagnosis of HDP was made according to the criteria of the ISSHP. A cardiologist performed maternal echocardiographies to calculate cardiac output (CO), total vascular resistance (TVR) and indexes of diastolic dysfunction evaluated with tissue Doppler (E'/A'). Results : We recruited 16 HDP-AGA, 20 HDP-IUGR, 14 severe IUGR and 19 controls. Heart rate (HR) and CO were significantly decreased and TVR significantly increased in HDP-IUGR and severe IUGR compared to controls. HDP-AGA shows a significantly decrease in E0/A0 compared to all other groups. Discussion : Hemodynamic parameters have different patterns in pregnancies complicated by HDP and/or IUGR. Severe IUGR and HDP-IUGR show a similar profile, despite the absence of abnormal blood pressure in the former group. HDP-AGA, that in our data showed a maternal predisposition to metabolic syndrome, has a different hemodynamic profile, with a predominant diastolic dysfunction respect to the group of HDP-IUGR.